Mechanistic Pathways for Peptidoglycan O-Acetylation and De-O-Acetylation - Sychantha, David; Brott, Ashley S.; Jones, Carys S.; Clarke, Anthony J. (Frontiers in Microbiology, 2018)
The post-synthetic O-acetylation of the essential component of bacterial cell walls, peptidoglycan (PG), is performed by many pathogenic bacteria to help them evade the lytic action of innate immunity responses. Occurring at the C-6 hydroxyl of N-acetylmuramoyl residues, this modification to the glycan backbone of PG sterically blocks the activity of lysozymes. As such, the enzyme responsible for this modification in Gram-positive bacteria is recognized as a virulence factor. With Gram-negative bacteria, the O-acetylation of PG provides a means of control of their autolysins at the substrate level. In this review, we discuss the pathways for PG O-acetylation and de-O-acetylation and the structure and function relationship of the O-acetyltransferases and O-acetylesterases that catalyze these reactions. The current understanding of their mechanisms of action is presented and the prospects of targeting these systems for the development of novel therapeutics are explored.